Upaya Kepala Sekolah Dalam Pembinaan Kedisiplinan Bagi Peserta Didik di SMP Islam Al Ma’arif 02 Malang - Rully Sofiana Devi; Ika Ratih Sulistiani; Muhammad Sulistiono (VICRATINA, 2019)
Various man in to face the change of attitude. Some of the people see the changes as a threat and some see it as a possibility for a batter life. There is none who be able to prevent from the alteration. Because of it happen any time of human life.in this era of globalization present accelerate the developments of the times in all aspects of life. Education is one of the most important supporting factors in addressing climate change. Of chourse, it must be supported by education institution that worthy of. For an instituation is a place of education. Change is expected to solve the various problems that education especially in matters of discipline expected the creation of the result of conducive for improving the quality of education and the development of human resources in order to prepare the next generation of indonesia future.